1991
DOI: 10.2105/ajph.81.11.1480
|View full text |Cite
|
Sign up to set email alerts
|

Black-white differences in infant mortality in 38 standard metropolitan statistical areas.

Abstract: Infrodudion ResultsThe US Black-White difference in the infant mortality rate has persisted. Lower rates have been reported for Blacks in the West than in the other three US census regions.' This report examines the Black-White difference in infant mortality rate in 38 large standard metropolitan statistical areas (SMSAs), including several in California, in relation to socioeconomic status indicators and an index of residential segregation. Residential segregation may be associated with such factors as the av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
65
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(68 citation statements)
references
References 4 publications
3
65
0
Order By: Relevance
“…And, several studies have demonstrated that African-American communities were more likely to be targeted for tobacco consumption compared to white communities. 36,37 Other studies have demonstrated a link between segregation and health disparities across a variety of unrelated health outcomes, such as infant mortality, 29,39,40 adult mortality, 30,[41][42][43] tuberculosis, 38,44 and hospital admissions. 45 However, segregation has not been well studied as a potential source of confounding, but it is potentially a substantial problem, which can lead to erroneous conclusions about the etiology of racial disparities in health.…”
Section: Introductionmentioning
confidence: 99%
“…And, several studies have demonstrated that African-American communities were more likely to be targeted for tobacco consumption compared to white communities. 36,37 Other studies have demonstrated a link between segregation and health disparities across a variety of unrelated health outcomes, such as infant mortality, 29,39,40 adult mortality, 30,[41][42][43] tuberculosis, 38,44 and hospital admissions. 45 However, segregation has not been well studied as a potential source of confounding, but it is potentially a substantial problem, which can lead to erroneous conclusions about the etiology of racial disparities in health.…”
Section: Introductionmentioning
confidence: 99%
“…2 Many studies have shown that black mortality rates are higher in metropolitan areas with high levels of segregation as compared to areas with lower levels of segregation. [3][4][5][6][7][8][9][10][11] The adverse effects on health are felt to occur through poorer residential area quality and its effects on health behaviors and health care, independent of individual and/or area level socioeconomic status (SES). 2 The studies cited above used various measures to define segregation, ranging from population composition 6,7,11,12 to more formally defined measures.…”
Section: Introductionmentioning
confidence: 99%
“…2 The studies cited above used various measures to define segregation, ranging from population composition 6,7,11,12 to more formally defined measures. [3][4][5][8][9][10] Though the use of population composition as a proxy for segregation is neither technically nor conceptually the same as the formal constructs, the studies that used population composition as a measure of segregation 6,7,11 have also found that black mortality rates are higher in areas with a high proportion of blacks. The segregation literature, [3][4][5][6][7][8][9][10] for the most part, has used large geographical areas as the unit of analysis or has compared smaller areas across a broad geography but generally not focused on the local impacts of segregation that result in areas with both low and high residential race/ethnic minority concentrations within a metropolitan area.…”
Section: Introductionmentioning
confidence: 99%
“…All residential segregation, although most dramatically in the African American community, has been shown to result in racial disparities in socioeconomic status and has been linked to health outcomes such as all-cause mortality [18,19], premature mortality [20], infant mortality [21,22] and tuberculosis [23].…”
mentioning
confidence: 99%